Ethics in doctorate research: A journey through research paradigms - Nur Nadiah Salihah, Mat Razali; Fernando, Yudi (Universiti Malaysia Pahang, 2024)
This study aims to explore the ethical research elements that doctorate students need to comply with in their research journey. This study will elucidate five philosophical paradigms in management research which are, positivism, critical realism, post modernism, interpretivism, and pragmatism. Examining critical aspects of positivism, critical realism, postmodernism, interpretivism, and pragmatism involved reviewing information from publications as part of the contextual analysis process. The research findings show there are five paradigm shifts in Business management studies and each of the paradigm have their uniqueness which assist the doctoral study to adopt and adapt the ethical research value their research process. The implication of this study will enhance the mastery of knowledge about the research paradigms. Hence, the doctorate students may have proper guideline in bring out their research ideas until research discussion with a well direction. Research paradigms known as the best research procedures to use when doing research in each of the paradigms under discussion were identified, along with suggested solutions to obstacles in this regard. It was recommended that prospective researchers be provided with suitable direction on selecting research paradigms for doctoral studies that comply with ethical standards. The research paradigm as one of the ways to comprehend the clear whole research direction including research design, research methodology, statistical analysis and etc.